2-Nitroimidazole based fluorescent probes for nitroreductase; monitoring reductive stress in cellulo. Issue 29 (17th July 2017) - Ao, X.; Bright, S. A.; Taylor, N. C.; Elmes, R. B. P.
Abstract : Two 2-nitroimidazole-1, 8-naphthalimide conjugates, 1 and2, have been synthesised as fluorescence probes for the detection of reductive stress in HeLa cells. Abstract : Two 2-nitroimidazole-1, 8-naphthalimide conjugates, 1 and2, have been synthesised as fluorescence probes for the detection of reductive stress in HeLa cells. The 4-substituted derivative1 was shown to act as a highly sensitive and selective substrate for nitroreductase where it exhibited a clear blue to green ratiometric fluorescence response visible to the naked eye. Moreover, biological studies demonstrated1 could be activated in cellulo where the impact of reductive stress was easily monitored using confocal microscopy and flow cytommetry.